Efficacy of a novel extract of fenugreek seeds in alleviating vasomotor symptoms and depression in perimenopausal women: A randomized, double‐blinded, placebo‐controlled study. Issue 12 (6th October 2020) - Khanna, Aman; John, Febi; Das, Syam; Thomas, Jestin; Rao, Jyoti; Maliakel, Balu; IM, Krishnakumar
Abstract: The present randomized, double‐blinded, placebo‐controlled study investigated the effect of a standardized fenugreek extract (FHE) on perimenopausal discomforts and its influence on hormonal balance and safety. Healthy women characterized with perimenopausal symptoms ( n = 48), as assessed by MRS questionnaire, were randomized either to FHE ( n = 24) or placebo ( n = 24) and supplemented with 250 mg × 2/day for 42 days. Both inter and intra‐group comparison revealed a significant improvement in somatic, psychological, and urogenital scores in FHE group, especially for hot flashes (25.9%), night sweats (26.5%), depression (31.8%), and insomnia (21.6%). Further hormone analysis revealed an enhancement in serum estradiol (18.9%), free testosterone (38.2%), and progesterone (19.9%) concentrations and a significant decrease in FSH (38.2%) and SHBG (21.1%) concentrations toward establishing a hormonal balance among FHE‐group; without significant changes in other clinical safety parameters. Thus, FHE supplementation offered a significant reduction in vasomotor effects and depression in perimenopausal women, without any adverse effects Practical applications: Fenugreek is a popular kitchen spice and Ayurvedic medicine for a variety of health conditions including diabetes, hypercholesterolemia, hepatotoxicity, gastritis, and also for a variety of hormone‐related health conditions such as sexual functions, lactation, osteoporosis, PCOS, and post/perimenopausal discomforts. Fenugreek is rich in alkaloids, steroidal saponins, flavonoids and 4‐hydroxyisoleucine. The present randomized‐controlled study investigated the plausible application of a standardized hydro‐ethanolic extract of fenugreek seeds (FHE) having a unique 3:1 ratio for protodioscin to trigonelline in the management of perimenopausal discomforts. It was observed that FHE at a dosage of 250 mg × 2/day for 42 days significantly reduced the discomforts, especially vasomotor symptoms and depression, and helped to attain a hormonal balance without any adverse effects or deviations in clinical safety parameters. Thus, FHE could be a potential natural agent for the management of post and perimenopausal discomforts and has to be explored in future studies. Abstract : A standardized hydro‐ethanolic extract of fenugreek seeds (FHE) having a unique 3:1 ratio for protodioscin to trigonelline in the management of Peri‐menopausal discomforts. FHE at a dosage of 250 mg × 2/day for 42 days significantly reduced the discomforts, especially vasomotor symptoms and depression, and helped to attain a hormonal balance without any adverse effects or deviations in clinical safety parameters. FHE could be a potential natural agent for the management of post and perimenopausal discomforts.